Effectiveness of Stellate Excision in Reducing Keloid Recurrence and Improving Aesthetic Outcomes in the Upper Third of the Ear - Di Pierro, Francesco; Loh, Sean Bo Jie; Chua, Nevin Yi Meng; D'Souza, Ayman Alwyn; Ng, Chew Lip (Facial Plastic Surgery, 2025)
Auricular keloids, particularly in the upper third of the ear, often recur after treatment and can cause aesthetic and functional deformities. This study assesses the effectiveness of stellate excision in reducing recurrence and improving cosmetic outcomes.Stellate excisions evolved from 19th-century wedge excisions, refined by 1960s otoplasty techniques to preserve ear shape and prevent deformities. Traditional skin flap techniques frequently show high recurrence rates and can compromise auricular contour, leading to unsatisfactory results.The ear, and specifically the upper third, is a challenging site for keloids due to its characteristic anatomy and susceptibility to mechanical stress during healing.Stellate excision allows for precise resection of keloids with back cuts and wedge extension to preserve ear shape and reduce tension.Forty adult patients with upper third keloids were retrospectively studied. All underwent stellate excision and standardized steroid injection follow-up.Complete excision with cartilage wedge resection, local flap closure, and layered suturing was performed under local anesthesia.Triamcinolone injections were administered at 2, 4, and 8 weeks postoperatively; follow-up continued for 24 months.Stellate excision showed a 95% success rate; future studies should assess broader anatomical applicability.Stellate excision is a reliable and cosmetically favorable method for managing upper third ear keloids, with a low recurrence rate.
Keywords: stellate excision; keloid; auricle; recurrence; scar management